Multidimensional Land-use Information for Local Planning and Land Resources Assessment in Indonesia: Classification Scheme for Information Extraction from High-Spatial Resolution Imagery - Projo Danoedoro (Faculty of Geography, Universitas Gadjah Mada, 2019)
Suitable land-cover/land-use information is rarely available in most developing countries, particularly when newness, accuracy, relevance, and compatibility are used as evaluation criteria. In Indonesia, various institutions developed their own maps with considerable differences in classification schemes, data sources and scales, as well as in survey methods. Redundant land-cover/land-use surveys of the same area are frequently carried out to ensure the data contains relevant information. To overcome this problem, a multidimensional land-use classification system was developed. The system uses satellite imagery as main data source, with a multi-dimensional approach to link land-cover information to land-use-related categories. The land-cover/land-use layers represent image-based land-cover (spectral), spatial, temporal, ecological and socio-economic dimensions. The final land-cover/land-use database can be used to derive a map with specific content relevant to particular planning tasks. Methods for mapping each dimension are described in this paper, with examples using Quickbird satellite imagery covering a small part the Semarang area, Indonesia. The approaches and methods used in this study may be applied to other countries having characteristics similar to those of Indonesia